Political affinity and investors' response to the acquisition premium in cross-border M&A transactions — A moderation analysis - Christian Fieberg; Kerstin Lopatta; Thomas Tammen; Sebastian A. Tideman (Strategic Management Journal, 2021)
This article investigates the moderating effect of political affinity between countries on investors' reactions to the premium in cross-border acquisitions (CBAs). Based on a sample of 1,183 CBAs between 1999 and 2018, we find that political affinity positively moderates the relationship between the acquisition premium and the acquiring and target firms' stock market return. We argue that investors use political affinity to assess the reliability of the premium (i.e., management's overall perception of a given deal's synergistic potential). This is in line with prior literature reasoning that, unlike strong political affinity, weak political affinity increases the likelihood of government intervention, decreases the likelihood of deal completion, and results in higher premiums to mitigate the previous effects, thus potentially increasing the likelihood of value destruction.
Keywords: 650; acquisition premium; cross-border mergers and acquisitions; investor reaction; moderation analysis; political affinity